High-impact ASA high rubber powder for automobiles

The preparation of modified silica and active silane seed emulsions is formed to form an optimized nuclear layer structure, which solves the problem of insufficient impact strength of existing ASA high-glue powder, and significantly improves its impact resistance and mechanical properties.

CN119143944AInactive Publication Date: 2024-12-17SHANDONG DONGLIN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411642550.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The impact strength of existing ASA high rubber powder is insufficient, making it difficult to meet the strict requirements of the automotive industry.

Method used

By preparing modified silica and active silane seed emulsions, nuclear polymerization and shell polymerization steps are adopted to form a core layer with nanosilicon dioxide as the innermost layer, silicone structure as the transition layer, and acrylate as the outermost layer using nuclear layer using nanosilicon dioxide as the innermost layer, silicone structure as the transition layer, and acrylate as the outermost layer using nuclear layer using nanosilicon dioxide as the innermost layer, silicone structure as the transition layer, and acrylate as the outermost layer using nuclear layer using nanosilicon dioxide as the innermost layer, Structure to improve the impact resistance of ASA high glue powder.

Benefits of technology

The impact strength, tensile strength and bending strength of ASA high rubber powder are significantly improved, and its impact resistance is enhanced, and the mechanical performance loss caused by inorganic organic interface incompatibility is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A high impact ASA high rubber powder for automobiles belongs to the technical field of high polymer materials, and the high impact ASA high rubber powder for automobiles is obtained through four steps of preparation of modified silicon dioxide, preparation of active silane seed emulsion, core polymerization and shell polymerization. According to the obtained high-impact-resistance ASA high rubber powder for the automobile, after ASA resin is prepared from 70 parts of SAN resin, 30 parts of high-impact-resistance ASA high rubber powder, 0.5 part of oxidized polyethlene wax and 1 part of carbon black, the measured tensile strength ranges from 57.3 MPa to 59.3 MPa, the measured bending strength ranges from 66.9 MPa to 68.7 MPa, the measured notch impact strength ranges from 21.5 MPa to 22.9 MPa, and the melt flow rate ranges from 30.1 g / 10 min to 31.8 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to high-impact ASA high-rubber powder for automobiles, belonging to the technical field of polymer materials. Background Art

[0002] Acrylonitrile-styrene-acrylate copolymer (ASA), also known as ASA high-rubber powder, is a ternary polymer with a core-shell two-phase structure and good impact resistance. This structure is formed by using polybutyl acrylate rubber as the core and using emulsion polymerization technology to graft styrene (St) and acrylonitrile (AN) onto the polybutyl acrylate (PBA) rubber core to form an ASA grafted polymer. Subsequently, the grafted polymer is mixed with styrene-acrylonitrile copolymer (SAN) to prepare ASA resin. ASA has good rigidity and toughness, high gloss, and weak plastic feel. It is an ideal material for making car grilles. However, with the rapid development of the automotive industry and the trend of lightweighting, the impact resistance of ASA high-rubber powder cannot fully meet the stringent requirements of the automotive industry. The industry is in urgent need of ASA high-rubber powder with excellent impact resistance to meet the needs of the automotive industry.

[0003] Chinese patent CN109293842A discloses an ASA resin high-rubber powder and a preparation method thereof, comprising the following steps: 1) preparation of seeds; 2) preparation of cores; 3) preparation of shells; 4) post-treatment; in steps 1) to 3), the emulsifier used is a mixture of anionic surfactants and nonionic surfactants, and the mass ratio of anionic surfactants to nonionic surfactants is 8 to 9:1; the reducing agent solution used is prepared by the following method: 0.1g of ferrous sulfate, 1.5g of sodium formaldehyde sulfoxylate and 2g of ethylenediaminetetraacetic acid are dissolved in 500g of deionized water. The synthesis process of the present invention has low temperature, low energy consumption, easy control and high conversion rate; great progress has been made in the impact strength of the obtained product. The cantilever beam notched impact strength of the ASA resin high-rubber powder obtained by this patent can only reach 7.5kJ / m 2 , it is difficult to meet the usage requirements of the automotive industry.

[0004] Chinese patent CN104231185A discloses an ASA resin high-rubber powder and its preparation method. It includes the following steps: adding deionized water, a diameter expander, an emulsifier, an acrylate monomer, a cross-linking agent, and an initiator into a reaction container to react to obtain an acrylate seed latex; taking the acrylate seed latex, adding the acrylate monomer, and reacting to obtain a core layer latex; adding styrene and acrylonitrile to the core layer latex, and grafting the monomers into the core layer latex to obtain a primary grafted polymer emulsion; mixing the remaining styrene and acrylonitrile, the emulsifier and deionized water, and emulsifying to a stable emulsion; adding the emulsion dropwise to the primary grafted polymer emulsion containing the initiator to react, and completing the secondary grafting polymerization by heating and aging, adding a composite antioxidant to the polymer emulsion, and coagulating, dehydrating, and drying to obtain an ASA resin high-rubber powder. The impact strength of the ASA resin high-rubber powder obtained by this patent is only 9.96kJ / m 2 , not ideal.

[0005] From the above, we can see that the impact strength of the current ASA high-rubber powder is relatively poor. Therefore, developing a high-impact ASA high-rubber powder for automobiles is of great practical significance for promoting the development of the automobile industry. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a high-impact ASA high-rubber powder for automobiles to achieve the following invention objectives: to prepare an ASA high-rubber powder with particularly excellent impact strength.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A high-impact ASA high-rubber powder for automobiles, wherein the high-impact ASA high-rubber powder for automobiles is obtained through four steps of preparing modified silicon dioxide, preparing active silane seed emulsion, core polymerization, and shell polymerization; The following are further improvements to the above technical solution: Step 1: Preparation of modified silica Add nano-silicon dioxide, toluene and methyl palmitate into a high-speed dispersion kettle, disperse vigorously at a speed of 9000-13000 rpm for 6-12 hours, reduce the dispersion speed to 2000-5000 rpm, then increase the temperature and keep the temperature constant at 80-110° C., then add trivinyl chlorosilane, react at the constant temperature for 6-11 hours, centrifuge, wash the separated solid with anhydrous ethanol for 3-5 times, put it into a vacuum drying oven at 40-60° C. and dry it for 4-8 hours to obtain modified silicon dioxide; The particle size of the nano silicon dioxide is 10-40 nm; The mass ratio of the nano silicon dioxide, toluene, methyl palmitate and trivinyl chlorosilane is 15-40:150-190:1-2.5:6-12.

[0008] Step 2: Preparation of active silane seed emulsion Sodium dodecylbenzene sulfonate and deionized water are added to a high-speed dispersing kettle, and the dispersing rate is controlled at 2000-5000 rpm. After the sodium dodecylbenzene sulfonate is completely dissolved, the dispersing rate is increased to 6000-9000 rpm. Then, active silane and modified silicon dioxide are added. After continuous high-speed dispersing for 10-16 hours, a uniform and stable white emulsion is obtained, which is the active silane seed emulsion. The active silane is one of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, trivinylsilane, 2-(divinylmethylsilyl)ethyltriethoxysilane, 1,1,3,3-tetramethyl-1,3-divinyldisilazane, and hexavinyldisiloxane; The mass ratio of the sodium dodecylbenzene sulfonate, deionized water, active silane and modified silicon dioxide is 1-3:110-180:10-20:2-8.

[0009] Step 3: Nuclear fusion Add the active silane seed emulsion into the polymerization kettle, evacuate the pressure in the polymerization kettle to -0.09~-0.08MPa, then introduce nitrogen to positive pressure, and then evacuate and introduce nitrogen again, after three cycles, under the protection of nitrogen, raise the temperature in the kettle and keep the temperature constant at 55~75°C, control the stirring rate at 500~1000 rpm, and drop the mixed solution of acrylate and initiator into the polymerization kettle at a speed of 0.1~0.6 g / sec. After the dropwise addition is completed, continue to stir and react at constant temperature for 3~6 hours to obtain a core polymerization emulsion; The mixed solution of acrylate and initiator is prepared by mixing butyl acrylate, 1,3-butanediol dimethacrylate, allyl methacrylate and tert-butyl hydroperoxide in a mass ratio of 10-30:2-6:25-45:1-3.5; The active silane seed emulsion, the mixed solution of acrylate and the initiator have a feed mass ratio of 3 to 10:2.

[0010] Step 4: Shell polymerization The core polymerization emulsion is kept at a constant temperature of 55-75° C., and under nitrogen protection, the stirring rate is controlled to be 500-1000 rpm, and then the shell monomer mixture is added dropwise to the core polymerization emulsion at a rate of 0.1-1.3 g / s. After the addition of the shell monomer mixture is completed, the reaction is continued at a constant temperature and stirred for 6-11 hours, and then cooled to room temperature to obtain a shell polymerization emulsion, and then a magnesium sulfate aqueous solution with a magnesium sulfate mass fraction of 5-8wt% is added to break the emulsion, and the filtrate is filtered after breaking the emulsion, and the filtrate is washed with water for 3-5 times, and then placed in a 65-80° C. oven for drying for 13-20 hours to obtain a high-impact ASA high-rubber powder; The shell monomer mixture is prepared by mixing acrylonitrile, styrene and tert-butyl hydroperoxide in a mass ratio of 15-40:35-75:0.6-2; The mass ratio of the core polymerization emulsion to the shell monomer mixture is 3-9:13; The feed mass ratio of the shell polymerization emulsion to the magnesium sulfate aqueous solution is 4-10:1.

[0011] Compared with the prior art, the present invention achieves the following beneficial effects: 1. The present invention uses trivinyl chlorosilane to modify the surface of nano-silica. There are a large number of hydroxyl groups on the surface of nano-silica. After reacting with trivinyl chlorosilane, the surface of nano-silica changes from being covered with hydroxyl groups to being covered with carbon-carbon double bonds. These carbon-carbon double bonds react with active silanes containing double bonds and acrylate raw materials during the core polymerization process. The reactive silanes have relatively high reactivity. The nano-silica covered with carbon-carbon double bonds will preferentially wrap a transition layer structure composed of an organic silicon, and then combine with a core layer composed of an acrylate raw material. Thus, a core layer structure is formed with nano-silica inorganic matter as the innermost layer, an organic silicon structure as the transition layer, and an acrylate organic structure as the outermost layer. In this core layer structure, the innermost layer has the strengthening and toughening effect of inorganic nano-silica. At the same time, the transition layer of the constructed organic silicon structure is used to avoid the loss of mechanical properties caused by the incompatibility of the organic-inorganic interface. Therefore, the ASA rubber powder obtained based on the above core layer structure will have very excellent impact resistance. 2. In the step of preparing the active silane seed emulsion of the present invention, the active silane added has a dual functional group reaction activity, one is the addition reaction activity of the carbon-carbon double bond, and the other is the high reaction activity of the active hydrogen or active hydroxyl groups on the three functional groups of siloxane, silazane or silane. The above two highly reactive sites will promote the modified silica to react preferentially with the active silane, thereby making the modified nano-silica preferentially wrapped with a transition layer structure composed of an organic silicon. It is precisely because of the organic silicon transition layer that the strengthening and toughening effect of the inorganic nano-silica is maximized, avoiding the loss of mechanical properties caused by the incompatibility of the inorganic and organic interfaces; 3. The high-impact ASA high-rubber powder for automobiles obtained by the present invention is made into ASA resin according to a formula of 70 parts of SAN resin, 30 parts of high-impact ASA high-rubber powder, 0.5 parts of oxidized polyethylene wax, and 1 part of carbon black. The measured tensile strength is 57.3~59.3MPa, the flexural strength is 66.9~68.7MPa, the notched impact strength is 21.5~22.9MPa, and the melt flow rate is 30.1~31.8g / 10min. DETAILED DESCRIPTION

[0012] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Example 1: A high impact ASA high glue powder for automobiles Step 1: Preparation of modified silica Add nano-silica, toluene and methyl palmitate into a high-speed dispersing kettle, disperse vigorously at a speed of 11000 rpm for 10 hours, reduce the dispersing speed to 4000 rpm, then increase the temperature and keep the temperature constant at 100°C, then add trivinyl chlorosilane, react at the constant temperature for 9 hours, centrifuge, wash the separated solid with anhydrous ethanol for 4 times, put it into a vacuum drying oven at 55°C and dry it for 7 hours to obtain modified silica; The particle size of the nano silicon dioxide is 30 nm; The mass ratio of the nano-silicon dioxide, toluene, methyl palmitate and trivinyl chlorosilane is 30:180:2:10.

[0014] Step 2: Preparation of active silane seed emulsion Sodium dodecylbenzene sulfonate and deionized water were added into a high-speed dispersing kettle, and the dispersing rate was controlled at 4000 rpm. After the sodium dodecylbenzene sulfonate was completely dissolved, the dispersing rate was increased to 7000 rpm. Then, active silane and modified silicon dioxide were added. After continuous high-speed dispersing for 15 hours, a uniform and stable white emulsion was obtained, which was the active silane seed emulsion. The active silane is 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane; The mass ratio of the sodium dodecylbenzene sulfonate, deionized water, active silane and modified silicon dioxide is 2:160:14:6.

[0015] Step 3: Nuclear fusion The active silane seed emulsion is added to the polymerization kettle, and the pressure in the polymerization kettle is evacuated to -0.084MPa, and then nitrogen is introduced to positive pressure, and then the vacuum is evacuated and nitrogen is introduced again. After three cycles, the temperature in the kettle is raised and kept constant at 65°C under nitrogen protection, and the mixed solution of acrylate and initiator is added dropwise to the polymerization kettle at a speed of 0.5g / sec at a stirring rate of 800 rpm. After the addition is completed, the reaction is continued at a constant temperature and stirred for 4 hours to obtain a core polymerization emulsion; The mixed solution of acrylate and initiator is prepared by mixing butyl acrylate, 1,3-butanediol dimethacrylate, allyl methacrylate and tert-butyl hydroperoxide in a mass ratio of 18:5:40:2; The active silane seed emulsion, the mixed solution of acrylate and the initiator have a feed mass ratio of 7:2.

[0016] Step 4: Shell polymerization The core polymerization emulsion was kept at a constant temperature of 70° C., and under nitrogen protection, the stirring rate was controlled to 800 rpm, and then the shell monomer mixture was added dropwise to the core polymerization emulsion at a rate of 1 g / sec. After the addition of the shell monomer mixture was completed, the reaction was continued at a constant temperature and stirred for 9 hours, and then cooled to room temperature to obtain a shell polymerization emulsion, and then a magnesium sulfate aqueous solution with a magnesium sulfate mass fraction of 6 wt% was added to break the emulsion, and the emulsion was filtered after breaking the emulsion. After washing the filtrate with water for 4 times, it was placed in a 75° C. oven and dried for 17 hours to obtain a high-impact ASA high-rubber powder; The shell monomer mixture is prepared by mixing acrylonitrile, styrene and tert-butyl hydroperoxide in a mass ratio of 35:70:1; The mass ratio of the core polymerization emulsion to the shell monomer mixture is 5:13; The feed mass ratio of the shell polymerization emulsion to the magnesium sulfate aqueous solution is 9:1.

[0017] Example 2: A high impact ASA high glue powder for automobiles Step 1: Preparation of modified silica Add nano-silica, toluene and methyl palmitate into a high-speed dispersing kettle, disperse vigorously at 9000 rpm for 6 hours, then reduce the dispersing rate to 2000 rpm, then increase the temperature and keep the temperature constant at 80°C, then add trivinyl chlorosilane, react at the constant temperature for 6 hours, centrifuge, wash the separated solid with anhydrous ethanol for 3 times, put it into a vacuum drying oven at 40°C and dry it for 4 hours to obtain modified silica; The particle size of the nano silicon dioxide is 10 nm; The mass ratio of the nano-silicon dioxide, toluene, methyl palmitate and trivinyl chlorosilane is 15:150:1:6.

[0018] Step 2: Preparation of active silane seed emulsion Sodium dodecylbenzene sulfonate and deionized water are added to a high-speed dispersing kettle, and the dispersing rate is controlled at 2000 rpm. After the sodium dodecylbenzene sulfonate is completely dissolved, the dispersing rate is increased to 6000 rpm, and then active silane and modified silicon dioxide are added. After continuing the high-speed dispersing for 10 hours, a uniform and stable white emulsion is obtained, which is the active silane seed emulsion; The active silane is trivinylsilane; The mass ratio of the sodium dodecylbenzene sulfonate, deionized water, active silane and modified silicon dioxide is 1:110:10:2.

[0019] Step 3: Nuclear fusion The active silane seed emulsion was added to the polymerization kettle, and the pressure in the polymerization kettle was evacuated to -0.09 MPa, and then nitrogen was introduced to positive pressure, and then the vacuum was evacuated and nitrogen was introduced again. After three cycles, the temperature in the kettle was raised and kept constant at 55° C. under nitrogen protection, and the mixed solution of acrylate and initiator was added dropwise to the polymerization kettle at a speed of 0.1 g / s under a stirring rate of 500 rpm. After the addition was completed, the reaction was continued at a constant temperature and stirred for 3 hours to obtain a core polymerization emulsion; The mixed solution of acrylate and initiator is prepared by mixing butyl acrylate, 1,3-butanediol dimethacrylate, allyl methacrylate and tert-butyl hydroperoxide in a mass ratio of 10:2:25:1; The active silane seed emulsion, the mixed solution of acrylate and the initiator have a feed mass ratio of 3:2.

[0020] Step 4: Shell polymerization The core polymerization emulsion was kept at a constant temperature of 55° C., under nitrogen protection, the stirring rate was controlled to 500 rpm, and then the shell monomer mixture was added dropwise to the core polymerization emulsion at a rate of 0.1 g / sec. After the addition of the shell monomer mixture was completed, the reaction was continued at a constant temperature and stirred for 6 hours, and then cooled to room temperature to obtain a shell polymerization emulsion, and then a magnesium sulfate aqueous solution with a magnesium sulfate mass fraction of 5wt% was added to break the emulsion, and the emulsion was filtered after breaking the emulsion. After washing the filtrate with water for 3 times, it was placed in a 65° C. oven and dried for 13 hours to obtain a high-impact ASA high-rubber powder; The shell monomer mixture is prepared by mixing acrylonitrile, styrene and tert-butyl hydroperoxide in a mass ratio of 15:35:0.6; The mass ratio of the core polymerization emulsion to the shell monomer mixture is 3:13; The feed mass ratio of the shell polymerization emulsion to the magnesium sulfate aqueous solution is 4:1.

[0021] Example 3: A high impact ASA high glue powder for automobiles Step 1: Preparation of modified silica Add nano-silica, toluene and methyl palmitate into a high-speed dispersing kettle, disperse vigorously at a speed of 13,000 rpm for 12 hours, reduce the dispersing speed to 5,000 rpm, then heat and keep the temperature constant at 110° C., then add trivinyl chlorosilane, react at the constant temperature for 11 hours, centrifuge, wash the separated solid with anhydrous ethanol for 5 times, put it into a vacuum drying oven at 60° C. and dry it for 8 hours to obtain modified silica; The particle size of the nano silicon dioxide is 40 nm; The mass ratio of the nano-silicon dioxide, toluene, methyl palmitate and trivinyl chlorosilane is 40:190:2.5:12.

[0022] Step 2: Preparation of active silane seed emulsion Sodium dodecylbenzene sulfonate and deionized water were added into a high-speed dispersing kettle, and the dispersing rate was controlled at 5000 rpm. After the sodium dodecylbenzene sulfonate was completely dissolved, the dispersing rate was increased to 9000 rpm. Then, active silane and modified silicon dioxide were added. After continuous high-speed dispersing for 16 hours, a uniform and stable white emulsion was obtained, which was the active silane seed emulsion. The active silane is 2-(divinylmethylsilyl)ethyltriethoxysilane; The mass ratio of the sodium dodecylbenzene sulfonate, deionized water, active silane and modified silicon dioxide is 3:180:20:8.

[0023] Step 3: Nuclear fusion The active silane seed emulsion is added to the polymerization kettle, and the pressure in the polymerization kettle is evacuated to -0.08MPa, and then nitrogen is introduced to positive pressure, and then the vacuum is evacuated and nitrogen is introduced again. After three cycles, the temperature in the kettle is raised and kept constant at 75°C under nitrogen protection, and the mixed solution of acrylate and initiator is added dropwise to the polymerization kettle at a speed of 0.6g / s under a stirring rate of 1000 rpm. After the addition is completed, the reaction is continued at a constant temperature and stirred for 6 hours to obtain a core polymerization emulsion; The mixed solution of acrylate and initiator is prepared by mixing butyl acrylate, 1,3-butanediol dimethacrylate, allyl methacrylate and tert-butyl hydroperoxide in a mass ratio of 30:6:45:3.5; The active silane seed emulsion, the mixed solution of acrylate and the initiator have a feed mass ratio of 10:2.

[0024] Step 4: Shell polymerization The core polymerization emulsion was kept at a constant temperature of 75° C., and under nitrogen protection, the stirring rate was controlled to be 1000 rpm, and then the shell monomer mixture was added dropwise to the core polymerization emulsion at a rate of 1.3 g / s. After the addition of the shell monomer mixture was completed, the reaction was continued at a constant temperature and stirred for 11 hours, and then cooled to room temperature to obtain a shell polymerization emulsion, and then a magnesium sulfate aqueous solution with a magnesium sulfate mass fraction of 8wt% was added to break the emulsion, and the emulsion was filtered after breaking the emulsion. After washing the filtrate with water for 5 times, it was placed in an oven at 80° C. and dried for 20 hours to obtain a high-impact ASA high-rubber powder; The shell monomer mixture is prepared by mixing acrylonitrile, styrene and tert-butyl hydroperoxide in a mass ratio of 40:75:2; The mass ratio of the core polymerization emulsion to the shell monomer mixture is 9:13; The feed mass ratio of the shell polymerization emulsion to the magnesium sulfate aqueous solution is 10:1.

[0025] Example 4: A high impact ASA high glue powder for automobiles The operation of step 1 is the same as that of embodiment 1; Step 2: Preparation of active silane seed emulsion The active silane is 1,1,3,3-tetramethyl-1,3-divinyldisilazane, and the other operations are the same as in Example 1; The operations of steps 3 and 4 are the same as those of Example 1.

[0026] Example 5: A high impact ASA high glue powder for automobiles The operation of step 1 is the same as that of embodiment 1; Step 2: Preparation of active silane seed emulsion The active silane is hexavinyl disiloxane, and the other operations are the same as in Example 1; The operations of steps 3 and 4 are the same as those of Example 1.

[0027] Comparative Example 1: Based on Example 1, step 1, preparing modified silicon dioxide, is not performed. In step 2, in preparing the active silane seed emulsion, 6 parts of modified silicon dioxide are replaced with 6 parts of deionized water. The specific operation is as follows: Step 1, preparing modified silicon dioxide is not performed; Step 2: Preparation of active silane seed emulsion The 6 parts of modified silicon dioxide were replaced by 6 parts of deionized water, and the other operations were the same as in Example 1; The operations of steps 3 and 4 are the same as those of Example 1.

[0028] Comparative Example 2: Based on Example 1, in step 2, in preparing the active silane seed emulsion, 14 parts of active silane were replaced with 14 parts of deionized water. The specific operation was as follows: The operation of step 1 is the same as that of embodiment 1; Step 2, in preparing the active silane seed emulsion, 14 parts of active silane were replaced by 14 parts of deionized water, and the other operations were the same as in Example 1; The operations of steps 3 and 4 are the same as those of Example 1.

[0029] Performance Test: The high flow and high impact ASA high rubber powder obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2 were added to a high-speed mixer according to a formula measured by weight: 70 parts of SAN resin, 30 parts of high impact ASA high rubber powder, 0.5 parts of oxidized polyethylene wax, and 1 part of carbon black. After being mixed evenly, they were extruded and granulated in a twin-screw extruder, and then added to an injection molding machine for injection molding to make test specimens. With reference to GB / T 1040.1-2018, GB / T 9341-2008, GB / T 1843-2008, ASTM G154, and GB / T3682.1-2018, tensile strength, flexural strength, notched impact strength, and melt flow rate were tested, wherein the melt flow rate test conditions were 220°C×10kg, and the test results are shown in Table 1: Table 1

[0030] From the data in Table 1, it can be seen that the notched impact strength of Examples 1-5 is all 21.5 kJ / m 2 The above have relatively good impact resistance; in Comparative Example 1 without adding modified silica, the tensile strength and flexural strength are reduced, the notched impact strength is reduced to 12.6 kJ / mol, and the melt flow rate is basically unchanged, which shows that modified silica has basically no negative impact on the tensile strength, flexural strength and melt flow rate of ASA high glue powder, but has a very significant positive effect on improving the impact strength. This may be because modified silica, as the innermost layer of the core-shell structure of ASA high glue powder, plays a strong toughening function of nano-inorganic materials. Therefore, in Comparative Example 1 without adding modified silica, the toughness is reduced too much, resulting in a very significant decrease in impact resistance; Comparative Example 2 does not add active silane, and the situation is similar to Comparative Example 1, but compared with the decrease between Comparative Example 1 and Example 1, the tensile strength and flexural strength are The reduction is slightly greater than that of Comparative Example 1, the reduction in notched impact strength is significantly greater than that of Comparative Example 1, and the melt flow rate is basically unchanged, which shows that the addition of active silane has a certain positive effect on the tensile strength and flexural strength, and has no effect on the melt flow rate. However, similar to modified silica, active silane plays a vital role in improving the impact resistance, and the improvement is slightly greater than that of modified silica. This may be because active silane, as a highly reactive silicone, can play a good elastic transition role between the inorganic reinforcement of modified silica and the organic core layer mainly composed of acrylate, that is, enhance the chemical bonding between the interface of inorganic silica and the interface of acrylate organic core layer, and minimize the loss of mechanical properties caused by the incompatibility between the inorganic and organic interfaces.

[0031] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high impact ASA high rubber powder for automobiles, Features: The high impact ASA high rubber powder for automobiles is obtained through four steps of preparing modified silicon dioxide, preparing active silane seed emulsion, core polymerization and shell polymerization; The modified silicon dioxide is prepared by the following method: adding nano silicon dioxide, toluene and methyl palmitate into a high-speed dispersion kettle, dispersing vigorously at a speed of 9000-13000 rpm for 6-12 hours, reducing the dispersion speed to 2000-5000 rpm, heating and keeping the temperature constant at 80-110° C., adding trivinyl chlorosilane, reacting at the constant temperature for 6-11 hours, centrifuging, washing the separated solid with anhydrous ethanol for 3-5 times, and drying it in a vacuum drying oven at 40-60° C. for 4-8 hours to obtain the modified silicon dioxide; The method for preparing the active silane seed emulsion is as follows: sodium dodecylbenzene sulfonate and deionized water are added into a high-speed dispersion kettle, the dispersion rate is controlled at 2000-5000 rpm, after the sodium dodecylbenzene sulfonate is completely dissolved, the dispersion rate is increased to 6000-9000 rpm, then active silane and modified silicon dioxide are added, and the high-speed dispersion is continued for 10-16 hours to obtain a uniform and stable white emulsion, which is the active silane seed emulsion; The active silane is one of 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane, trivinylsilane, 2-(divinylmethylsilyl)ethyltriethoxysilane, 1,1,3,3-tetramethyl-1,3-divinyldisilazane, and hexavinyldisiloxane; The core polymerization method comprises: adding active silane seed emulsion into a polymerization kettle, evacuating the pressure in the polymerization kettle to -0.09-0.08 MPa, introducing nitrogen to positive pressure, evacuating the pressure again, introducing nitrogen, and repeating this cycle three times. Then, under nitrogen protection, the temperature in the kettle is raised and kept constant at 55-75° C., and a mixed solution of acrylate and initiator is dripped into the polymerization kettle at a speed of 0.1-0.6 g / s while controlling the stirring rate to 500-1000 rpm. After the dripping is completed, the reaction is continued at a constant temperature and stirred for 3-6 hours to obtain a core polymerization emulsion. The shell polymerization method comprises: keeping the core polymerization emulsion at a constant temperature of 55-75°C, under nitrogen protection, controlling the stirring rate to 500-1000 rpm, then dripping the shell monomer mixture into the core polymerization emulsion at a rate of 0.1-1.3 g / s, and after the shell monomer mixture is dripped, continuing the constant temperature stirring reaction for 6-11 hours, cooling to room temperature to obtain the shell polymerization emulsion, and then adding a magnesium sulfate aqueous solution with a magnesium sulfate mass fraction of 5-8wt% to break the emulsion, filtering after breaking the emulsion, washing the filtrate with water for 3-5 times, and drying it in a 65-80°C oven for 13-20 hours to obtain a high-impact ASA high-rubber powder.

2. The high impact ASA high rubber powder for automobiles according to claim 1, Features: The particle size of the nano silicon dioxide is 10-40 nm; The mass ratio of the nano silicon dioxide, toluene, methyl palmitate and trivinyl chlorosilane is 15-40:150-190:1-2.5:6-12.

3. The high impact ASA high rubber powder for automobiles according to claim 1, Features: The mass ratio of the sodium dodecylbenzene sulfonate, deionized water, active silane and modified silicon dioxide is 1-3:110-180:10-20:2-8.

4. The high impact ASA high rubber powder for automobiles according to claim 1, Features: The mixed solution of acrylate and initiator is prepared by mixing butyl acrylate, 1,3-butanediol dimethacrylate, allyl methacrylate and tert-butyl hydroperoxide in a mass ratio of 10-30:2-6:25-45:1-3.5; The active silane seed emulsion, the mixed solution of acrylate and the initiator have a feed mass ratio of 3 to 10:

2.

5. The high impact ASA high rubber powder for automobiles according to claim 1, Features: The shell monomer mixture is prepared by mixing acrylonitrile, styrene and tert-butyl hydroperoxide in a mass ratio of 15-40:35-75:0.6-2; The mass ratio of the core polymerization emulsion to the shell monomer mixture is 3-9:13; The feed mass ratio of the shell polymerization emulsion to the magnesium sulfate aqueous solution is 4-10:1.

Citation Information

Patent Citations

  • Preparation method of ASA (acrylonitrile styrene acrylate) powder

    CN104231185A

  • Matte organic silicon high-impact toughening agent and preparation method thereof

    CN112724335A

  • Thermoplastic resin and process for reducing the same

    US5218014A

Cited By

  • High-impact high-gloss ASA resin and preparation method thereof

    CN119798880A

  • Method for preparing low-temperature-resistant ASA (acrylonitrile-styrene-acrylate) resin by continuous bulk process

    CN122188060A